Parvalbumin interneurons: the dark and bright sides of a key playmaker of neural circuits and behavior - Wirk, Eesha; Quairiaux, Charles; Marissal, Thomas (Frontiers in Cellular Neuroscience, 2025)
With their morphological and electrophysiological properties as well as exceptional connectivity, parvalbumin interneurons play a major role in the dynamics of the neural circuits of the hippocampus and cortex, along with associated cognitive functions. Their dysfunction, which is sometimes reversible, contributes to significant disruptions in network activity and behavioral deficits related to various diseases such as epilepsies or neuropsychiatric disorders. In this Mini Review, we present these parvalbumin interneurons, their characteristics, pathophysiological roles, and propose avenues for future investigations.